Comparing the effect of a desensitizing material and a self-etch adhesive on dentin sensitivity after periodontal surgery: a randomized clinical trial - Hila Hajizadeh; Atefeh Nemati-Karimooy; Sara Majidinia; Amir Moeintaghavi; Marjaneh Ghavamnasiri (Korean Academy of Conservative Dentistry, 2017)
Objectives This double-blind randomized placebo-controlled clinical trial evaluated the ability of a desensitizing agent and a self-etch adhesive on cervical dentin sensitivity (CDS) after periodontal surgery. Materials and Methods Ninety hypersensitive teeth of 13 subjects were included in the study. After periodontal surgery, the teeth of each posterior sextant treated with one of the following materials: G1: Clearfil S3 Bond (Kuraray Dental), G2: Gluma Desensitizer (Heraeus Kulzer), and G3: placebo (water). The sensitivity was assessed using evaporative stimuli before treatment (baseline, T0), 1 day after treatment (T1), after 1 week (T2), and after 1 month (T3) according to visual analog scale (VAS). Results Following the treatment, all the 3 groups showed significant reduction of CDS in T1 compared to T0. Reduction of CDS between T1 and T2 was observed only in G1 but there was no significant difference between T2 and T3 in this group. Although we observed a significant difference in T3 compared to T1 and T2 in G2 and G3, comparison of treatment groups in each assessment time showed a significant difference only in T3. According to paired comparison, this was due to the difference between G2 and G3. Conclusions Dentin sensitivity following periodontal surgery will decrease spontaneously over time, but treating the sensitive teeth with Gluma Desensitizer and Clearfil S3 Bond can have some benefits.